The inheritance : the world Obama confronts and the challenges to American power - Sanger, David E. (New York : Harmony Books, 2009)
The chief Washington correspondent of the New York Times offers a riveting insider's account describing the national security crises that will confront America's next president from a nuclear Iran to the lock up of Chinese oil supplies in Africa.
Pt. 1. Iran : the Mullahs' Manhattan Project. Decoding Project 111 -- Regime-change fantasies -- Ahmadinejad's monologue -- The Israel option -- Pt. 2. Afghanistan : how the good war went bad. The Marshall plan that wasn't -- The other'mission accomplished' -- Pt. 3. Pakistan :'how do you invade an ally?' Secrets of Chaklala Cantonment -- Crossing the line -- Pt. 4. North Korea : the nuclear renegade that got away. Kim Jong-Il 8, Bush 0 -- Cheney's lost war --'Everything is Appomattox -- Pt. 5. China : new torch, old dragons. Generation Lenovo -- The puncture strategy --Pt. 6. The three vulnerabilities. Deterrence 2.0 -- The invisible attack -- Dark angel -- Obama's challenge.
Includes bibliographical references (p. [465]-486) and index.
Keywords: Obama, Barack; Bush, George W. -- 1946- -- Influence; National security -- United States -- History -- 21st century; United States -- Foreign relations -- 2001-2009.; United States -- Military policy